Comparing STEM and contextual approaches' impact on students' motivation and learning in acid-base materials - Aji, Latief Susila; Zamhari, Muhammad; Saputra, Febri Ilham; Masrukhah, Dewi (IAIN Palangka Raya, 2024)
This study aimed to compare the impact of science, technology, engineering, and mathematics (STEM) and contextual approaches on students' motivations for learning and achievements in chemistry lessons focused on acid-base materials. A quasiexperimental design with a non-equivalent control group was used, and the participants were 66 students of class XI Science students from State Senior High School 1 (SMA N 1) Kalibawang. Data collection instruments included pre and post-questionnaires and test questions. The findings revealed significant differences in students' learning motivations and achievements between the STEM and contextual approaches to acid-base materials. Both approaches improved students' learning motivations, with the STEM approach yielding higher gains.